From: A framework for the extended evaluation of ABAC policies
τ_{1}((a,v)) | = | a _{ v} |
τ_{1}(¬t_{1}) | = | τ_{0}(t_{1}) |
\(\tau _{1}(\mathop {\sim } t_{1})\) | = | τ_{1}(t_{1}) |
τ_{1}(E_{1}(t_{1})) | = | τ_{⊥}(t_{1}) |
τ_{1}(t_{1} t_{2}) | = | τ_{1}(t_{1})∧τ_{1}(t_{2}) |
τ_{1}(t_{1}⊓t_{2}) | = | τ_{1}(t_{1})∧τ_{1}(t_{2}) |
\(\tau _{1}(t_{1} \mathbin {\vartriangle } t_{2})\) | = | (τ_{1}(t_{1})∧¬τ_{0}(t_{2}))∨(τ_{1}(t_{2})∧¬τ_{0}(t_{1})) |
τ_{1}(t_{1} t_{2}) | = | τ_{1}(t_{1})∨τ_{1}(t_{2}) |
τ_{1}(t_{1}⊔t_{2}) | = | (τ_{1}(t_{1})∧¬τ_{⊥}(t_{2}))∨(τ_{1}(t_{2})∧¬τ_{⊥}(t_{1})) |
\(\tau _{1}(t_{1} \triangledown t_{2})\) | = | τ_{1}(t_{1})∨τ_{1}(t_{2}) |
π_{1}(1) | = | true |
π_{1}(0) | = | false |
π_{1}((t,p_{1})) | = | τ_{1}(t)∧π_{1}(p_{1}) |
π_{1}(¬p_{1}) | = | π_{0}(p_{1}) |
\(\pi _{1}(\mathop {\sim } p_{1})\) | = | π_{1}(p_{1}) |
π_{1}(E_{1}(p_{1})) | = | π_{⊥}(p_{1}) |
π_{1}(p_{1} p_{2}) | = | π_{1}(p_{1})∧π_{1}(p_{2}) |
π_{1}(p_{1}⊓p_{2}) | = | π_{1}(p_{1})∧π_{1}(p_{2}) |
\(\pi _{1}(p_{1} \mathbin {\vartriangle } p_{2})\) | = | (π_{1}(p_{1})∧¬π_{0}(p_{2}))∨(π_{1}(p_{2})∧¬π_{0}(p_{1})) |
π_{1}(p_{1} p_{2}) | = | π_{1}(p_{1})∨π_{1}(p_{2}) |
π_{1}(p_{1}⊔p_{2}) | = | (π_{1}(p_{1})∧¬π_{⊥}(p_{2}))∨(π_{1}(p_{2})∧¬π_{⊥}(p_{1})) |
\(\pi _{1}(p_{1} \triangledown p_{2})\) | = | π_{1}(p_{1})∨π_{1}(p_{2}) |